Pilot study of ultrasound-guided microwave ablation for inactivating excess remnant thyroid after surgery in patients with differentiated thyroid cancer - Yihao Chen; Rongwei Hu; Chunchun Jin; Leidan Huang; Yiqin Lin; Bingzi Zou; Xiaorui Liu; Zhilin Li; Zhengyi Li; Weizong Liu (BMC Cancer)
Abstract Objectives To evaluate the safety and efficacy of ultrasound (US)-guided microwave ablation (MWA) for inactivating excess remnant thyroid (RT) after surgery in patients with differentiated thyroid cancer (DTC). Methods This study was registered in the Chinese Clinical Trial Registry under the identifier ChiCTR2200063200 on September 1, 2022. This study enrolled consecutive postsurgery DTC patients who were scheduled for radioactive iodine ablation (RAI) therapy. These patients exhibited excess RT, which was removed via MWA. Changes in RT volume/weight before and after MWA, as well as alterations in laboratory parameters, were assessed. Complications arising from MWA were documented and monitored. Results Twenty-three patients participated in the study. Following US-guided MWA, there was a statistically significant decrease in the volume/weight of RT, from [2.90 (1.78, 4.28)] mL/[2.66 (1.63, 3.92] g to (0.93 ± 0.43) mL/(0.83 ± 0.40) g (P < 0.001). Nineteen patients had an RT weight < 1 g post-MWA. An observed threshold effect between TSH levels and post-MWA follow-up time revealed an inflection point at 17.0 days, with TSH levels increasing by 2.5 mU/L per day from 0 to 17.0 days (P < 0.001), peaking above 30 mU/L on day 17.0. The TSH level subsequently decreased by 1.6 mU/L per day (P = 0.028) after 17.0 days. No serious complications were noted. Conclusions US-guided MWA is a relatively safe and effective method for inactivating excess RT after surgery and represents a potentially innovative minimally invasive approach. The relationship between TSH and follow-up time after MWA for inactivating excess RT reveals a threshold effect, aiding in determining the optimal timing for RAI therapy post-MWA, yet its universal applicability necessitates additional investigation.